2022
DOI: 10.1002/smll.202106357
|View full text |Cite
|
Sign up to set email alerts
|

Micropore‐Forming Gelatin Methacryloyl (GelMA) Bioink Toolbox 2.0: Designable Tunability and Adaptability for 3D Bioprinting Applications

Abstract: It is well‐known that tissue engineering scaffolds that feature highly interconnected and size‐adjustable micropores are oftentimes desired to promote cellular viability, motility, and functions. Unfortunately, the ability of precise control over the microporous structures within bioinks in a cytocompatible manner for applications in 3D bioprinting is generally lacking, until a method of micropore‐forming bioink based on gelatin methacryloyl (GelMA) was reported recently. This bioink took advantage of the uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 60 publications
1
61
0
Order By: Relevance
“…GelMA is a temperature-sensitive material that experiences a gel-to-solution (gel-to-sol) transition when the temperature is elevated . Rheological analysis of porous hydrogel was first performed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…GelMA is a temperature-sensitive material that experiences a gel-to-solution (gel-to-sol) transition when the temperature is elevated . Rheological analysis of porous hydrogel was first performed.…”
Section: Resultsmentioning
confidence: 99%
“…GelMA is a temperature-sensitive material that experiences a gel-tosolution (gel-to-sol) transition when the temperature is elevated. 21 Rheological analysis of porous hydrogel was first It was reported that GelMA was photocured at 4 °C after physical gelation up to 10 5 Pa, which was 8 times higher than that at 37 °C. 26 To mimic the stiffness of the spinal cord tissue (500−1500 Pa), 27 an adaptive storage modulus scaffold for the spinal cord was obtained and the GelMA and porous pre-gel solution were tested at a concentration of 6 wt %, preheated at 37 °C, and then photocured at 5 mW•cm −2 for 30 s. The storage modulus nearly achieved maximum, as shown in Figure 1D,E.…”
Section: Rheological Analysis Of Porous Hydrogelmentioning
confidence: 99%
See 2 more Smart Citations
“…GelMA, as a transparent material, fully meets the requirements of the corneal stroma for transparency, and GelMA can satisfy the biocompatibility and mechanical strength requirements for producing biomaterials, as opposed to other biomaterials made from hydrogels. GelMA offers a good habitat for many types of cells to live in, since it is biocompatible [ 92 ], chemically adaptable [ 93 ], and biodegradable [ 88 ]. According to earlier studies, when cells are grown in three-dimensionally organized hydrogels, they have the ability to modify their surroundings to facilitate migration and spread [ 94 ].…”
Section: Research Into Gelma Materials In Corneal Stromal Regenerationmentioning
confidence: 99%